Oral mucosal alterations among the institutionalized elderly in Brazil - Raquel Conceição Ferreira; Cláudia Silami de Magalhães; Allyson Nogueira Moreira (Sociedade Brasileira de Pesquisa Odontológica, 2010)
This study determined the prevalence of oral mucosal alterations and associated factors among the institutionalized elderly in Brazil. Data were collected through a structured questionnaire, a review of their medical records and an intra-oral examination. A sample of 335 individuals over 60 years of age was randomly selected. In total, 646 alterations were diagnosed; 59.1% were variations of the normal oral mucosa. The most frequent variation consisted of sublingual varicosities (51.6%). Denture stomatitis (15.2%) and denture hyperplasia (12.8%) were the most frequent lesions. Elderly patients who wore dentures had a significantly higher prevalence of oral mucosal lesions (p = 0.00) than those that didn't wear dentures. There was a high prevalence of variations of the normal oral mucosa and of mucosal lesions, especially denture-induced lesions, among the institutionalized elderly.